Apakah terapi pengendalian plak dapat menurunkan keparahan rinitis alergika pada anak? (Does oral plaque control therapy reduce severity of allergic rhinitis in children?) - Haryono Utomo; Darmawan Setijanto (Dental Journal (Majalah Kedokteran Gigi), 2005)
Allergic rhinitis is one of the most common ailments in children. In clinical practice approximately 50% of patients with symptoms of rhinitis are diagnosed with non-allergic rhinitis. Positive skin prick test or specific IgE in vitro tests that are relevant to aeroallergens are conclusive diagnostic of allergic rhinitis. However, simple diagnostic method such as "sneezing sign" has already proved to be reliable. Hypersensitive children have humoral immune system (Th2) which release inflammatory factors in the presence of allergen or infection that contribute to allergic response. Immunological reactions occurred and antibodies concentration arise, especially specific IgE instead of IgG because of the isotype switching. A lot of procedures such as allergen avoidance, medication and immunotherapy were done in allergic rhinitis management. However, oral plaque controls were not the point of interest in this case. The aim of this study is to find out the effectiveness of oral plaque control in the reduction of severity of allergic rhinitis symptoms using symptom scores. Fifty children, male and female aged 8–14 years, subjective diagnosed as allergic rhinitis using "sneezing sign" were included in this study. Oral plaque control procedures were done by polishing and flossing followed by 4 days of gargling with 1% povidone iodine. Clinical result showed that after 3 days, oral plaque control 2.925 times more effective than control group. The conclusion was oral plaque control is effective reducing the severity of allergic rhinitis symptoms.